Enhancing Mathematical Reasoning through Contextual Mathematics Learning Using Biological Contexts in Basic Mathematics - Gelar Dwirahayu; Mardiana Zulfa (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2026)
This study analyzes the enhancement of students' mathematical reasoning abilities in a Basic Mathematics course through the implementation of context-based learning utilizing biological contexts. A pre-experimental method with a one-group pretest-posttest design was employed. The research was conducted during the odd semester of the 2025/2026 academic year within the Tadris Biology Study Program at UIN Syarif Hidayatullah Jakarta, involving a purposive sample of 94 students. Data were collected using both test and non-test instruments. The content validity of the four-item essay test was quantitatively verified using Aiken’s V index, indicating high validity, while instrument reliability was confirmed via Cronbach's Alpha (α = 0.82). Data analysis involved descriptive statistics, paired t-tests, Normalized Gain (N-gain) scores, and Cohen’s d effect size to evaluate the magnitude of improvement. The results demonstrated a statistically significant enhancement in students' mathematical reasoning across all indicators. The mean scores (on a scale of 1–4) for constructing justification increased from 2.6 to 3.3, drawing conclusions from 2.5 to 3.2, and mathematical manipulation from 2.8 to 3.4. Conversely, the capacity to verify argument validity showed a limited gain, rising from 2.4 to 2.7. The effect size analysis revealed a robust effect, confirming that biology-contextualized mathematics learning substantially develops procedural and constructive reasoning, whereas evaluative reasoning requires more targeted pedagogical interventions